Signal detection of ferric carboxymaltose-induced serious adverse events: disproportionality analysis of FAERS and VigiBase data and systematic review of case reports. - Galigutta, Reddikumar Reddy; Thomas, Christy; Rathod, Mahesh; Hasik, P. N.; Ray, R. S.; Prakash, Jai; Undela, Krishna (European Journal of Clinical Pharmacology, 2025)
Purpose: The recent surge in serious adverse events (SAEs) and deaths associated with ferric carboxymaltose (FCM) underscores the importance of evaluating its safety profile. Methods: We conducted a retrospective case/non-case study from Q4 of 2003 to Q4 of 2024 data on FCM in the FDA Adverse Event Reporting System (FAERS) and VigiBase databases. Signal detection was performed using proportional reporting ratio (PRR), reporting odds ratio (ROR), and information component (IC). The influence of concomitant medication on the identified signal was assessed and refined using Open Vigil 2.1. Additionally, to identify case reports on FCM-induced adverse events, a comprehensive search was performed in PubMed, Google Scholar, and Scopus databases from inception to April 12, 2025. Results: In the FAERS database, 46 deaths were reported in connection with FCM, though no significant death signal was observed (PRR = 0.3, LB (lower bound) ROR = 0.2, IC025 = − 2.3). Nonetheless, positive safety signals emerged for SAEs such as anaphylactic shock (PRR = 3.9, LB ROR = 2.3, IC025 = 1.0), circulatory collapse (PRR = 14.6, LB ROR = 10.5, IC025 = 3.1), respiratory distress (PRR = 9.6, LB ROR = 7.1, IC025 = 2.6), hypophosphatemia (PRR = 520.7, LB ROR = 530.1, IC025 = 8.0), and arrhythmia (PRR = 3.3, LB ROR = 2.2, IC025 = 1.0). After meticulously refining our analysis to account for the influence of concomitant medications, we observed that the strength of all signals remained unchanged, except for respiratory distress, bradycardia, hypotension, abdominal pain, and urticaria. Analysis of VigiBase data revealed 42 reported fatal cases and potential signals for hypersensitivity (PRR = 4.5, LB ROR = 4.4, IC025 = 2.1), anaphylactic shock (PRR = 2.3, LB ROR = 1.9, IC025 = 0.9), circulatory collapse (PRR = 7.2, LB ROR = 6.0, IC025 = 2.5), respiratory distress (PRR = 6.9, LB ROR = 5.7, IC025 = 2.5), and hypophosphatemia (PRR = 245.1, LBROR = 234.8, IC025 = 7.5) with Ferinject. The systematic review of 11 case reports emphasized SAEs linked to FCM, thereby strengthening this association. Conclusion: This study reveals that FCM carries SAEs. Providers must weigh the benefits and risks on a case-by-case basis, considering patient-specific factors. Continuous monitoring and further research are crucial for the safe use of FCM in iron deficiency anemia.